Effect of γ-irradiation on the structure of high density polyethylene composites with GaAs and GaAs<Te> fillers - Gadzhieva, N.N.; Akhmedova, G.B. (Вопросы атомной науки и техники, 2020)
IR-Fourier spectroscopy was used to study structural changes in γ-irradiated high density polyethylene composites with GaAs and GaAs<Te> semiconductor fillers at room temperature. From the dose dependence of the crystallinity degree of the HDPE/GaAs and HDPE/GaAs<Te> composites, it was found that the HDPE/GaAs<Te> composites are more radiation-resistant in the absorbed dose region Φγ = 5…150 kGy compared to the HDPE/GaAs composites. The observed change in the degree of crystallinity is associated with a change in the supramolecular structure of γ-irradiated composites. Метод ІЧ-фур’є-спектроскопії застосовано при вивченні структурних змін у γ-опромінених композитах поліетилену високої щільності (ПЕВЩ) з напівпровідниковими наповнювачами GaAs і GaAs<Te> при кімнатній температурі. За дозовою залежністю ступеня кристалічності композитів ПЕВЩ/GaAs і ПЕВЩ/GaAs<Te> встановлено, що композити ПЕВЩ/GaAs<Te> у порівнянні з композитами ПЕВЩ/GaAs є більш радіаційно-стійкими в області поглиненої дози Φγ = 5…150 кГр. Спостережувані зміни ступеня кристалічності пов’язані зі зміною надмолекулярної структури γ-опромінених композитів. Метод ИК-фурье-спектроскопии применен при изучении структурных изменений в γ-облученных композитах полиэтилена высокой плотности (ПЭВП) с полупроводниковыми наполнителями GaAs и GaAs<Te> при комнатной температуре. По дозовой зависимости степени кристалличности композитов ПЭВП/GaAs и ПЭВП/GaAs<Te> установлено, что композиты ПЭВП/GaAs<Te> по сравнению с композитами ПЭВП/GaAs являются более радиационно стойкими в области поглощенной дозы Φγ = 5…150 кГр. Наблюдаемые изменения степени кристалличности cвязаны с изменением надмолекулярной структуры γ-облученных композитов.